Uilenspiegel van Leuven. (Leuven : [Vlaamschen Gouwbond] L. Lekenne (2 jun 1918) Pros Haesaerts (1 sep 1918), 1918)
Redactie: Leo Magits, L. Peerenboom, W. van Grootven, J.F. RaymaekersBeheer/Administratie: Capucienenvoer 41, LeuvenDrukker/Drukkerij: Drukkerij van den Vlaamschen Gouwbond, Capucienenvoer 41, Leuven ; De Fakkel, Rattemanspoort, Leuven (2 jun. 1918)
Periodiciteit: wekelijksEerste nr.: 3 feb 1918
Nederlands
Krant
Keywords: gemeentebeleid; Vlaamse Beweging; activisme; krant; Leuven